The interplay between shame and religious pathology in Korean culture : a pastoral and anthropological assessment within the Korean Presbyterian Church - Jung, Yeun Chul (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2011.